KESIAPAN MASYARAKAT DALAM IMPLEMENTASI ADAPTASI KEBIASAAN BARU DI MASA PANDEMI COVID - 19 - Windu Santoso; Sri Sudarsih (Viva Medika, 2021)
At this time, Indonesia is preparing to enter a new normal life phase in the face of the Corona Virus pandemic. Several forms of changes or new transformations which later gave birth to the term "New Normal or New Habit Adaptation", namely changes in behavior to continue carrying out normal activities but with the addition of implementing health protocols to prevent transmission of the corona virus. The purpose of this study was to determine the readiness of the community in implementing adaptation. new habit. The research design used was a survey research design with a sample of 403 respondents in the district and city of Mojokerto. Data collection was carried out using a questionnaire which was distributed via google form. The data analysis used is descriptive analysis with frequency distribution. The results showed that a small proportion of respondents who were ready to implement the adaptation of new habits were 39.0% while those who were not ready were 30.8%. Every individual must have the desire to return to normal activities, be able to return to work, school, and interact with one another and do other activities in order to remain productive during a pandemic. We can do this if we can adapt to new habits, namely by applying the discipline of healthy living to each of us. The community's unpreparedness is due to not being used to new behaviors so that adaptation needs to be improved. Adaptation of new habits is an obligation for every individual and is a collective concern to break the chain of Covid-19 transmission.